Pendampingan Pelaku Usaha UMKM Makanan dalam Meningkatkan Promosi Digital Melalui Penggunaan Canva pada Bentoday Jakarta Barat - Pepi Permatasari; Sri Wahyuningsih; Sigit Nurcahyono; Wahyumi Ekawanti (Pusat Riset dan Inovasi Nasional, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting the growth and stability of the national economy (Endra et al., 2024), particularly in the ever-expanding culinary sector. However, MSMEs often face challenges in creating visually appealing and professional promotional elements. One example is BentoDay, a food business in West Jakarta that still relies on simple promotions through social media without optimal content packaging. This activity aims to improve the digital promotional capacity of MSMEs through a training and mentoring program focused on creating logos and product catalogs using Canva. Canva is a digital-based visual design tool that is easy to use, even for beginners, to create content such as posters, banners, and social media promotional materials (Akbar et al., n.d.). This training was conducted through a series of activities, starting with initial observation, direct training, intensive mentoring, and evaluation of participants' designs. The results showed that participants were able to independently produce promotional materials, such as logos and product catalogs, with more attractive and consistent designs. In addition to improving design skills, this training also had a positive impact on MSMEs' digital marketing strategies. Good visual design has been shown to increase consumer appeal and product sales. Thus, mastering digital skills is crucial for strengthening brand identity and expanding market reach (Andari, Sari, & Hidayat, 2025). The use of Canva has proven effective in supporting the digital promotional transformation of MSMEs to become more competitive in the digital era.